Voxelotor (GBT440) in pediatric sickle cell disease: A review - Sri Lakshmi Jamalapur; Alexander K. Glaros; Yaddanapudi Ravindranath (Pediatric Hematology Oncology Journal, 2024)
Sickle cell disease (SCD) was first described in 1910 in African Americans, and the mutant hemoglobin S (HbS) was identified by electrophoresis in 1948. Sickle cell disease is the first genetic disease to be molecularly defined - a single point mutation in the β-globin gene (GAG→GTG) results in substitution of valine for glutamic acid at amino acid residue 7 (including the starting methionine). Pharmacological intervention to correct the defect at a molecular/protein level has proven complex. The only established curative therapy is hematopoietic stem cell transplantation, with recent gene therapy approvals providing hope for the same. Herein, we discuss voxelotor, a drug designed to reverse the hemoglobin polymerization defect caused by the β7Glu > Val substitution in the hemoglobin molecule.